2015
DOI: 10.1016/j.neuroimage.2014.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Role of white-matter pathways in coordinating alpha oscillations in resting visual cortex

Abstract: In the absence of cognitive tasks and external stimuli, strong rhythmic fluctuations with a frequency ≈ 10 Hz emerge from posterior regions of human neocortex. These posterior α-oscillations can be recorded throughout the visual cortex and are particularly strong in the calcarine sulcus, where the primary visual cortex is located. The mechanisms and anatomical pathways through which local \alpha-oscillations are coordinated however, are not fully understood. In this study, we used a combination of magnetoencep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 85 publications
5
31
0
Order By: Relevance
“…The outer retinal layer thickness in the latter group was positively related to alpha band connectivity. A potential explanation may again be that optic neuritis causes damage to white matter tracts, which are especially known to be mediating alpha band oscillations 29. For the MSNON group, we found that delta band connectivity was related to thickness of the outer retinal layers.…”
Section: Discussionmentioning
confidence: 68%
“…The outer retinal layer thickness in the latter group was positively related to alpha band connectivity. A potential explanation may again be that optic neuritis causes damage to white matter tracts, which are especially known to be mediating alpha band oscillations 29. For the MSNON group, we found that delta band connectivity was related to thickness of the outer retinal layers.…”
Section: Discussionmentioning
confidence: 68%
“…1). We used the widely-used and freely available AAL template (Tzourio-Mazoyer et al, 2002) to parcellate the brain into 90 non-cerebellar regions in line with previous studies of resting-state MEG data (Cabral et al, 2014b; Hindriks et al, 2015; Brookes et al, 2016). Note however that, although this anatomy-derived parcellation serves for the purpose of the current work, it is unlikely to perform as well as a function-derived parcellation involving PCA (Baker et al, 2014; Colclough et al, 2015) .…”
Section: Methodsmentioning
confidence: 99%
“…A scalar implementation of the LCMV beamformer was applied to estimate the source level activity of the MEG sensor data at each brain area (Van Veen et al, 1997, Sekihara et al, 2001, Woolrich et al, 2011. We used the widely-used and freely available AAL template (Tzourio-Mazoyer et al, 2002) to parcellate the brain into 90 non-cerebellar regions in line with previous studies of resting-state MEG data (Cabral et al, 2014b, Hindriks et al, 2015, Brookes et al, 2016. Note however that, although this anatomy-derived parcellation serves for the purpose of the current work, it is unlikely to perform as well as a function-derived parcellation involving PCA (Baker et al, 2014, Colclough et al, 2015.…”
Section: Meg Data In Source Spacementioning
confidence: 99%